Risk factors for immune-related adverse effects during CPI therapy in patients with head and neck malignancies – a single center study - Jungbauer, Frederic; Affolter, Annette; Brochhausen, Christoph; Lammert, Anne; Ludwig, Sonja; Merx, Kirsten; Rotter, Nicole; Huber, Lena (Frontiers in Oncology, 2024)
Introduction: Checkpoint inhibitors, such as PD1 inhibitors, represent an important pillar in the therapy of advanced malignancies of the head and neck region. The most relevant complications are immune-related adverse effects (irAEs), which represent an immense burden for patients. Currently, no sufficient stratification measures are available to identify patients at increased risk of irAEs. The aim of this retrospective study was to examine whether demographic, histopathological, clinical, or laboratory values at the start of CPI therapy represent a risk factor for the later occurrence of autoimmune complications.Material and Methods: Data from 35 patients between 2018 and 2021 who received therapy with nivolumab or pembrolizumab for head and neck malignancy were analyzed and assessed for any associations with the subsequent occurrence of irAEs.Results: IrAE developed in 37% of patients, with pneumonitis being the most common form (14%). Pneumonitis was found in patients with an average significantly lower T-stage of primary tumors. An increase in basophilic leukocytes was found in patients with dermatitis later in the course. When thyroiditis developed later, the patients had a higher CPS score and lower monocyte levels.Discussion: Even though individual laboratory values at the beginning of therapy might show a statistical association with the later occurrence of irAEs, neither demographic, histopathological, nor laboratory chemistry values seem to be able to generate a sound and reliable risk profile for this type of complication. Therefore, patients need to be educated and sensitized to irAEs, and regular screening for irAEs should be carried out.